The Relationship of Dietary Habits on The Incidence of Hypertension in The Elderly in Rw 07, Sumur Batu District, Central Jakarta and Its Review According to Islamic Views - Naila Nur Fauziah; Syarif, Irfan; Mukhtar, Diniwati; Astiwara, Endy M (Fakultas Kedokteran Universitas YARSI, 2025)
Hypertension is a chronic condition commonly experienced by the elderly, with a high prevalence in Indonesia. This condition is caused by structural changes in blood vessels, such as lumen narrowing, stiffening of vessel walls, and reduced elasticity, which lead to increased blood pressure. One of the primary risk factors for hypertension is an unhealthy diet, including high sodium and fat consumption. This study aims to explore the relationship between dietary habits and the incidence of hypertension among elderly individuals in RW 07, Sumur Batu Village, Central Jakarta, from an Islamic perspective. This research employs a quantitative approach with an analytical cross-sectional design. The sample consists of 55 elderly individuals selected through purposive sampling. Data were directly collected through interviews using a dietary habit questionnaire based on the Food Frequency Questionnaire (FFQ) and blood pressure measurements with a sphygmomanometer. Statistical analysis using the chi-square test was conducted to identify the relationship between dietary habits and hypertension incidence. The majority of respondents had irregular dietary patterns, with high salt and fat consumption as dominant factors. The analysis revealed a significant relationship between dietary habits and hypertension (p < 0.05). Elderly individuals with irregular dietary habits were at a higher risk of developing hypertension compared to those with healthy dietary patterns. Adopting dietary practices aligned with the Islamic principles of halalan thayyiban can help prevent hypertension by emphasizing the importance of consuming nutritious and balanced food. Unhealthy dietary habits are significantly associated with hypertension in the elderly. Community-based health education, including religious approaches, is necessary to raise awareness about the importance of healthy eating in preventing hypertension.